Analisis Leader Member Exchange, Keseimbangan Kehidupan Kerja, Dan Komitmen Organisasional terhadap Intention Turnover - Noor Arifin; Hesti Latifatul Fauziah (Fakultas Ekonomi dan Bisnis Universitas Islam Nahdlatul Ulama Jepara, 2024)
Research aim of this research is to analyze the influence the variables Leader Member Exchange, Work-Life Balance, and Organizational Commitment to Turnover Intentions employees on PT Pijar Sukma Jepara. Kinds of this research is quantitative. The population was 60 employees, with sampling all population (saturated sample technique). The data analysis used Multiple Linear Regression Analysis and Hypothesis Test. The results shows that Leader Member Exchange has a negative effect to Turnover Intention with t-value -5.177 > t-table -1.672 and significant value 0.000 < 0.05. Work Life Balance has a negative effect to Turnover Intention with t-value -1.912 > t table -1.672 and significant value 0.025 < 0.05. Organizational Commitment has a negative effect to Turnover Intention with t-value of -2.513 > t table 1.67203 and significant value 0.015 < 0.05. Simultaneously F-table is 26.282 > 2.76 and significant value 0,000 < 0.05. So it can be concluded that Leader Member Exchange (X1), Work Life Balance (X2), and Organizational Commitment (X3) simultaneously have a positive and significant effect on the Turnover Intention Variable.